Immuno-Modulatory Effects of Intervertebral Disc Cells - Bermudez-Lekerika, Paola; Crump, Katherine B.; Tseranidou, Sofia; Nüesch, Andrea; Kanelis, Exarchos; Alminnawi, Ahmad; Baumgartner, Laura; Muñoz-Moya, Estefano; Compte, Roger; Gualdi, Francesco; Alexopoulos, Leonidas G.; Geris, Liesbet; et al. (Frontiers in Cell and Developmental Biology, 2022)
Lower back pain (LBP) is a highly prevalent, chronic, and costly medical condition predominantly triggered by interverbal disc degeneration (IDD). IDD is often caused by structural and biochemical changes in intervertebral discs (IVD) that prompt a pathologic shift from an anabolic to catabolic state, affecting extracellular matrix (ECM) production, enzyme generation, cytokine and chemokine production, neurotrophic and angiogenic factor production. The IVD is an immune-privileged organ. However, during degeneration immune cells and inflammatory factors can infiltrate through defects in the cartilage endplate and annulus fibrosus fissures, further accelerating the catabolic environment. Remarkably, though, catabolic ECM disruption also occurs in the absence of immune cell infiltration, largely due to native disc cell production of catabolic enzymes and cytokines. An unbalanced metabolism could be induced by many different factors, including a harsh microenvironment, biomechanical cues, genetics, and infection. The complex, multifactorial nature of IDD brings the challenge of identifying key factors which initiate the degenerative cascade, eventually leading to back pain. These factors are often investigated through methods including animal models, 3D cell culture, bioreactors, and computational models. However, the crosstalk between the IVD, immune system, and shifted metabolism is frequently misconstrued, often with the assumption that the presence of cytokines and chemokines is synonymous to inflammation or an immune response, which is not true for the intact disc. Therefore, this review will tackle immunomodulatory and IVD cell roles in IDD, clarifying the differences between cellular involvements and implications for therapeutic development and assessing models used to explore inflammatory or catabolic IVD environments.